Application of Home Made Ag2S Electrode in Alkaline Media - Rajbhandari, A; Yadav, AP; Pradhananga, RR; Manandhar, K; Durante, C; Gennarro, A; Favaro, G (Scientific World, 2010)
Home made silver sulphide ion selective electrode was prepared and applied for argentometric titration in alkaline media for the determination of thiamine hydrochloride.The amount of thiamine hydrochloride estimated from titration of ionisable chloride with silver nitrate was found to be 637 mg/g of the vitamin B1 tablet. This result is in agreement with the value obtained from ion chromatographic (IC) and cyclic voltammetric (CV) techniques. In presence of chloride from other sources, these techniques fail, but thiamine in pharmaceutical preparation, however, can be determined by potentiometric titration in highly alkaline medium using silver- sulphide membrane electrode with silver nitrate solution at which there is no interference due to the presence of chloride from other sources. The results showed that home made silver- sulphide electrode can be used as an indicator electrode for the potentiometric determination of thiamine in pharmaceutical preparation. Keywords: Silver sulphide electrode; Potentiometric titration; Thiamine; Vitamin B1. DOI: 10.3126/sw.v8i8.3853 Scientific World Vol.8(8) 2010 pp.69-72